2010
DOI: 10.1002/ana.22107
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of JC virus DNA in blood and urine from natalizumab‐treated patients

Abstract: Measuring JCV DNA in blood or urine with currently available methods is unlikely to be useful for predicting PML risk in natalizumab-treated MS patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
50
3
4

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 98 publications
(62 citation statements)
references
References 15 publications
5
50
3
4
Order By: Relevance
“…Patients who are found to be JCV-seronegative should be followed for seroconversion repeatedly during immunosuppressive treatment. By contrast, several studies have demonstrated that screening for JCV DNA in blood, CSF, or urine does not enhance the ability to predict development of PML 29,30 .…”
Section: Rheumatologymentioning
confidence: 94%
“…Patients who are found to be JCV-seronegative should be followed for seroconversion repeatedly during immunosuppressive treatment. By contrast, several studies have demonstrated that screening for JCV DNA in blood, CSF, or urine does not enhance the ability to predict development of PML 29,30 .…”
Section: Rheumatologymentioning
confidence: 94%
“…2,4,5 In one of the largest studies, 5 urinary JCV-DNA could not be detected in 1 of 3 patients who subsequently developed PML; urinary JCV excretion was detected frequently and did not increase during natalizumab treatment. Thus, predictive values of either positive or negative tests appear to be low.…”
Section: Megan Alcauskas MD and Robert C Griggs Mdmentioning
confidence: 97%
“…Thus, predictive values of either positive or negative tests appear to be low. 5 Using urinary JCV-DNA analysis, a false-negative rate of the 2-step anti-JCVantibody ELISA of approximately 2.7% can be calculated. 4 Due to lack of biomaterial we were not able to determine the rate of false-negative findings of anti-JCV serology in our cohort.…”
Section: Megan Alcauskas MD and Robert C Griggs Mdmentioning
confidence: 99%
“…Following initial infection, the virus persists in kidneys and in other tissues, including the brain. In immunologically normal patients this JCV persistence only results in recurrent episodes of asymptomatic viruria [184].…”
Section: Progressive Multifocal Leukoencephalopathymentioning
confidence: 99%